EFFECT OF GARLIC (Allium sativun) ON GROWTH PERFORMANCE, SURVIVAL AND BODY COMPOSITION OF Heterobranchus bidorsalis FINGERLINGS - Malud, Malud Mohammed; Hassan, Mohammed Zakariya; Abatcha, Goni Tahir (FUDMA Journal of Sciences, 2026)
Aquaculture production in developing countries is constrained by high feed costs and reliance on synthetic growth promoters. This study evaluated the effect of dietary garlic (Allium sativum) supplementation on the growth performance, nutrient utilization, survival, apparent digestibility, carcass composition and economic efficiency of Heterobranchus bidorsalis fingerlings. A total of 180 fingerlings (8.55 ± 0.15 g) were randomly distributed into five dietary treatments consisting of a control diet and garlic-supplemented diets at 10, 20, 30, and 40 g kg⁻¹, with each treatment replicated. Fish were fed a 40% crude protein diet for sixteen weeks. Growth performance indices, feed utilization parameters, apparent nutrient digestibility, carcass composition, water quality parameters, and cost–benefit analysis were evaluated. Results showed that fish fed the 30 g kg⁻¹ garlic diet recorded the highest weight gain (165.22 g), specific growth rate (0.03 % day⁻¹), condition factor (3.37), survival rate (95%), protein efficiency ratio (2.87), and the lowest feed conversion ratio (1.06). Apparent protein and lipid digestibility, as well as carcass crude protein content (73.35%), were also highest at this inclusion level. Water quality parameters remained within acceptable limits throughout the experimental period. Economic analysis indicated that the 30 g kg⁻¹ garlic diet was the most profitable. The study concludes that dietary garlic at 30 g kg⁻¹ can be used as natural growth promoter for Heterobranchus bidorsalis culture.